2010
DOI: 10.1038/bmt.2009.351
|View full text |Cite
|
Sign up to set email alerts
|

HLA-mismatched hematopoietic SCT without in vitro T-cell depletion for myelodysplastic syndrome

Abstract: Allogeneic hematopoietic SCT (HSCT) is currently the only curative treatment for myelodysplastic syndrome (MDS). However, many patients cannot find an HLA-matched donor. We have developed a new protocol for HLA-mismatched (including haploidentical) HSCT using G-CSF-primed BM plus G-CSF-mobilized PBSCs without in vitro T-cell depletion. A total of 36 patients diagnosed with high-risk MDS (RAEB (refractory anemia with excess blasts) or RAEBt (RAEB in transformation)) underwent transplantation from HLA-mismatched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 22 publications
(28 reference statements)
1
16
1
Order By: Relevance
“…88,89 Similar results were also reported in 36 myelodysplastic syndrome high-risk/RAEB-t (refractory anemia with excess blasts in transformation) patients who underwent transplantation from combined GBM with GPB (5 μg/kg per day G-CSF for 4-5 days) haplotype-mismatched sibling donors. 90 Rapid and sustained engraftment, without significant increase of GVHD, was also reported in 29 patients with combined GBM with GPB by Wang et al 91 The same team further confirmed their findings in another one-arm study of 756 patients, who received unmanipulated combined GBM and GPB (5 μg/kg per day G-CSF for 6 days). In that study, the median time for neutrophil and platelet engraftment was 13 and 16 days, respectively.…”
Section: Gbm From Hla-identical Sibling Donorssupporting
confidence: 73%
“…88,89 Similar results were also reported in 36 myelodysplastic syndrome high-risk/RAEB-t (refractory anemia with excess blasts in transformation) patients who underwent transplantation from combined GBM with GPB (5 μg/kg per day G-CSF for 4-5 days) haplotype-mismatched sibling donors. 90 Rapid and sustained engraftment, without significant increase of GVHD, was also reported in 29 patients with combined GBM with GPB by Wang et al 91 The same team further confirmed their findings in another one-arm study of 756 patients, who received unmanipulated combined GBM and GPB (5 μg/kg per day G-CSF for 6 days). In that study, the median time for neutrophil and platelet engraftment was 13 and 16 days, respectively.…”
Section: Gbm From Hla-identical Sibling Donorssupporting
confidence: 73%
“…There was no difference in the incidence and severity of aGVHD and cGVHD with HLA disparity, which was consistent with our previous results. [3][4][5][6][7][8][9] Although not being statistically significant, there are trends for a difference in diagnosis repartition between the CRD and IRD group (P ¼ 0.079). This may have an impact on GVHD occurrence.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] By this protocol, promising results have been achieved. [6][7][8][9] In this study, we compared the clinical outcomes of patients with hematological malignancies who underwent HLAhaploidentical HSCT, between CRD (n ¼ 30) and immediate related donor (IRD) groups (n ¼ 120) in the GIAC protocal.…”
Section: Introductionmentioning
confidence: 99%
“…Survival was 42% for patients with <15% myeloblasts and 0% for more advanced disease; day-100 (1-year) TRM was 9% (32%). Chen et al reported on 36 patients with high-risk MDS who underwent HLA-mismatched/HLA-haploidentical HCT with G-CSF-primed marrow and G-CSF-mobilized PBPCs, and showed a 2-year RFS of 65% [73]. Patients transplanted within 7 months of diagnosis had better outcomes (89% RFS) than those transplanted later (43%).…”
Section: What Can Patients Expect From Hct?mentioning
confidence: 99%